(untitled) (Contemporary Mathematics, 2024)
The main purpose of this manuscript is to provide a generalization of the concept of a 2-metric and prove some fixed point results for θ-type contractions. In this paper, we proved that a mapping T that is orbitally continuous, satisfying a θ-type contraction as a result of a relation between a pair of generalized 2-metrics and if one of the spaces is T-orbitally complete, then the mapping T has a fixed point.